2016
DOI: 10.1007/s12298-016-0374-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of in vitro embryo maturation, plantlet regeneration and transformation efficiency from alfalfa (Medicago sativa L.) somatic embryos using Cuscuta campestris extract

Abstract: Developmental deficiency of somatic embryos and regeneration to plantlets, especially in the case of transformation, are major problems of somatic embryo regeneration in alfalfa. One of the ways to overcome these problems is the use of natural plant regulators and nutrients in the culture medium of somatic embryos. For investigating the influence of Cuscuta campestris extract on the efficiency of plant regeneration and transformation, chimeric tissue type plasminogen activator was transferred to explants using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
5
0
8
Order By: Relevance
“…Proline had no visible impact on the shoot proliferation of nodal explant of R. canina. This amino acid was previously reported to be effective in somatic embryogenesis in certain plant species [44,45]. Although proline at the maximum concentration (2 g/l) improved shoot length and leaf number, it failed to stimulate shoot regeneration in the nodal explant of R. canina and thus it is not suggested to be used for direct in vitro regeneration of this plant.…”
Section: Discussionmentioning
confidence: 99%
“…Proline had no visible impact on the shoot proliferation of nodal explant of R. canina. This amino acid was previously reported to be effective in somatic embryogenesis in certain plant species [44,45]. Although proline at the maximum concentration (2 g/l) improved shoot length and leaf number, it failed to stimulate shoot regeneration in the nodal explant of R. canina and thus it is not suggested to be used for direct in vitro regeneration of this plant.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of somatic embryogenesis carried out in several plant species have demonstrated this low or non-existent rate of conversion of embryos to seedlings, such as, Oplopanax elatus (Nakai) Nakai (Moon et al, 2013), Manihot esculenta Crantz (Vidal et al, 2014), Medicago sativa L. (Amini;Deljou;Nabiabad, 2016), Crataegus spp. (Taimori et al, 2016) and Coffea arabica and C. canephora (Etienne et al, 2018).…”
Section: Callus Histological Analysismentioning
confidence: 99%
“…Растения указанного рода встречаются, например, в Ираке [2], Иране [3,4], Китае [5], Ливане [6], Нигерии [7], Египте [8,9], Индии [10,11], Италии [12,13], Тунисе [14], Турции [15,16], России [17]. Из видового разнообразия рода Cuscuta можно выделить такого представителя, как Cuscuta campestris (повилика полевая), который представляет собой интересный объект с точки зрения фитохимического изучения [18][19][20] и спектра биологической активности [21][22][23].…”
Section: Introductionunclassified